Utilization of Media In Physical Education Learning for Elementary School Students - Silvi Aryanti; Samsul Azhar; Ahmad Rifai Azani; Wahyu Indra Bayu; Bogy Restu Ilahi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this study was to determine the use of learning media, namely using Sparkol Videoscribe in Physical Education learning for elementary school students of class V MI Nurul Yaqiin. This research is a qualitative research with descriptive method. Data analysis using observation, interviews and documentation. The research subjects used 22 fifth grade students. The results showed that the use of learning media using Sparkol Videoscribe was good and quite interesting. The material can be understood even though the learning is done from home. The existence of sparkol videoscribe-based learning media, the steps of the practical material presented by the teacher can be seen. The results of the practice carried out by students and then students send videos through the whatsapp group can be seen that students are able to practice the material according to the steps correctly. The Sparkol Videoscribe learning media can make physical education learning interesting and varied. The material provided by the teacher is not monotonous and the students are very interested in participating in the learning. The implication of this research is that sparkol videoscribe-based learning media can be used for learning physical education for elementary school students.